Underlying structure of bulky oxide nodule on alumina-forming austenitic stainless steel. (June 2015) - Kang, Jun-Yun; Ha, Heon-Young; Jang, Min-Ho; Moon, Joonoh; Suh, Dong-Woo; Lee, Tae-Ho
Abstract : The bulky oxide nodule and its underlying structure were investigated in an alumina-forming austenitic steel exposed to dry air at 1053 K for 336 h. Some bulky oxide nodules were found to be attached on globular phases in the matrix. By combined application of electron backscattering diffraction and energy dispersive X-ray spectroscopy, the bulky nodule was identified as Cr-rich M3 O4 underlying which was Nb-rich MO2 . Thermodynamic calculation suggested that the MO2 was transformed from the primary NbC near surface.